Synthesis and Characterization of Hydroxyapatite from Polymesoda placans Shell using Wet Precipitation Method - Charlena; Irma Herawati Suparto; Daniel Putra Oktavianus Laia (JURNAL BIOS LOGOS, 2023)
Hydroxyapatite (HAp) is a bioceramic material that has chemical components similar to bone and teeth. Further development and exploration of calcium sources continued to be done to synthesize HAp. The purpose of this research was to synthesize HAp from the shell of Polymesoda placans using the wet precipitation method. The synthesis used in this study was by reacting calsium hydroxide from the shells and diammonium hydrogen phosphate as a phosphate precursor with the sintering temperatures of 600, 800, 1000, and 1100 oC and pH 9, 10 dan 11. Based on the X-ray diffraction spectrum, the best sintering temperature was 1000 oC with pH of 10-11 because it revealed the highest crystallinity (90.1 %). Functional groups analyzed by Fourier transform infrared showed that there were PO43-, OH- , and CO32- groups in the HAp. Scanning electron microscope analysis showed uniform granule particles with particle sizes of 0.3-1.6 µm.